2022
DOI: 10.1002/adma.202200152
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry‐Leaves‐Derived Red‐Emissive Carbon Dots for Feeding Silkworms to Produce Brightly Fluorescent Silk

Abstract: luminescent, and low-cost substances seems to be the optimal strategy to produce fluorescent silk. [9][10][11] Carbon dots (CDs) are the most competitive candidates for the above target, because they have shown outstanding biocompatibility and superior fluorescence in previous research such as bioimaging, [12,13] drug delivery, [14,15] and photothermal therapy. [16,17] In fact, many CDs are made from biomass, which guarantees the biosafety, low price, and green chemistry in CDs production. [18] In comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 54 publications
2
80
0
Order By: Relevance
“…In 2010, Zhao et al synthesized nitrogen-doped g-CDs with chitosan and D (+) glucosamine hydrochloride by hydrothermal method, [33] which laid a certain foundation for the preparing more g-CDs and opened the door to synthesize of g-CDs with natural products as carbon sources. More and more scholars are now synthesizing g-CDs with excellent properties, such as, Liu et al [34] used mulberry leaves to synthesize the deepest red emission, hydrophobic g-CDs (R-CDs). Based on the advantages of R-CDs' near-infrared fluorescence, good hydrophobicity, and biocompatibility, they were safely fed to silkworms, which could grow normally and healthily after eating R-CDs and showed red fluorescence, cocoon breaking moths for mating could produce normal fluorescent eggs, however, the control group of silkworms did not show red fluorescence.…”
Section: Synthesis Methods Of Green Carbon Dotsmentioning
confidence: 99%
“…In 2010, Zhao et al synthesized nitrogen-doped g-CDs with chitosan and D (+) glucosamine hydrochloride by hydrothermal method, [33] which laid a certain foundation for the preparing more g-CDs and opened the door to synthesize of g-CDs with natural products as carbon sources. More and more scholars are now synthesizing g-CDs with excellent properties, such as, Liu et al [34] used mulberry leaves to synthesize the deepest red emission, hydrophobic g-CDs (R-CDs). Based on the advantages of R-CDs' near-infrared fluorescence, good hydrophobicity, and biocompatibility, they were safely fed to silkworms, which could grow normally and healthily after eating R-CDs and showed red fluorescence, cocoon breaking moths for mating could produce normal fluorescent eggs, however, the control group of silkworms did not show red fluorescence.…”
Section: Synthesis Methods Of Green Carbon Dotsmentioning
confidence: 99%
“…These kind of bioinspired modification methods are probably quite effective for improving the biomedical performance for cell culture and tissue repair. Another example would be intrinsically luminescent silk materials produced through genetic engineering or altering the food of silkworms [ [169] , [170] , [171] , [172] , [173] , [174] , [175] , [176] ], which are useful for special biomedical usage. In addition, improved cytocompatibility, conductivity and mechanical properties, such as elastomeric properties and stretchability, may also be achieved through chemical or physical modification progress.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…glucose, lignin, fruits, vegetables, and leaves). [139][140][141][142][143][144][145][146] Ye reported the red C-dots using coal as the precursor, with a QY of 0.4% to 1.1%. 140 Ran used a thermalassisted electrochemical method to produce C-dots using coal slice as the precursor.…”
Section: Other Precursorsmentioning
confidence: 99%
“…101 As earth-abundant and low-cost resources, biomass has been widely used for the synthesis of C-dots with tunable colours. 142,143 Liu et al reported the preparation of C-dots made from mulberry leaves. 143 The as-prepared CDs have a main emission peak at 676 nm with a shoulder at 725 nm, possessing a full width at half maximum of 20 nm and a QY of 73%.…”
Section: Synthesis and Optical Properties Of Red/near-infrared C-dotsmentioning
confidence: 99%